2022
DOI: 10.1253/circj.cj-22-0143
|View full text |Cite
|
Sign up to set email alerts
|

Is Combination Therapy the Key for Treatment of Heart Failure With Mid-Range or Preserved Ejection Fraction?

Abstract: Heart failure (HF) is a major clinical syndrome that is a leading cause of death and morbidity, 1,2 and is closely associated with neurohormonal activation. 3 The left ventricular ejection fraction (LVEF) is widely used to guide treatment for patients with HF, predominantly because of previous clinical trial inclusion criteria, as the studies that reported beneficial effects of treatment mostly included patients with HF and reduced LVEF (HFrEF). However, given that HFrEF accounts for only 30-40% of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Fourth, we analyzed both HFrEF and HFmrEF, although the prognostic impact of FMHF has not been tested in randomized clinical trials for patients with HFmrEF. However, a series of studies have already shown that FMHF is likely associated with improved prognosis in patients with HFmrEF 40 44 , and the latest European Society of Cardiology and the American College of Cardiology, American Heart Association, and Heart Failure Society of America guidelines provide IIb recommendations to FMHF for patients with HFmrEF in terms of reducing HF hospitalization and death 2 , 3 . Finally, we included patients who discontinued some medications and initiated other medications in each group, which might complicate the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we analyzed both HFrEF and HFmrEF, although the prognostic impact of FMHF has not been tested in randomized clinical trials for patients with HFmrEF. However, a series of studies have already shown that FMHF is likely associated with improved prognosis in patients with HFmrEF 40 44 , and the latest European Society of Cardiology and the American College of Cardiology, American Heart Association, and Heart Failure Society of America guidelines provide IIb recommendations to FMHF for patients with HFmrEF in terms of reducing HF hospitalization and death 2 , 3 . Finally, we included patients who discontinued some medications and initiated other medications in each group, which might complicate the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…4 Key questions for clinicians raised by these new guidelines are about the efficacy and tolerability/safety of combinations of these different therapies for patients with HFmrEF/HFpEF. [7][8][9] Although the three classes of treatment are believed to work through distinct mechanisms and should have additive benefits, the evidence that this is the case is limited. Indeed, in the EMPEROR-Preserved trial, the effect of empagliflozin on first and recurrent heart failure hospitalizations was more pronounced in MRA non-users (HR 0.60, 95% CI 0.47-0.77) than in MRA users (HR 0.90, 95% CI 0.68-1.19; p interaction = 0.038) although the interaction for the primary composite outcome including cardiovascular death was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…Key questions for clinicians raised by these new guidelines are about the efficacy and tolerability/safety of combinations of these different therapies for patients with HFmrEF/HFpEF 7–9 . Although the three classes of treatment are believed to work through distinct mechanisms and should have additive benefits, the evidence that this is the case is limited.…”
Section: Introductionmentioning
confidence: 99%
“…ՍԱ հիվանդների մոտ ՁՓ ԱՖ-ի փոփոխությունը կարող է լինել անգամ առանց միջամտության կամ որպես բուժման հետևանքով առաջացած բարելավում [17,18,36,37]: ՍԱ-ի բուժումը, հատկապես այն հիվանդների մոտ, ովքեր ունեն ԱՖ<45%, և որոնք ստանում են համապատասխան բուժում ուղեկցող հիվանդությունների կապակցությամբ, ևս շատ կարևոր է հիվանդության բարենպաստ ելքի համար [11,17]։ Այդ իսկ պատճառով պարտադիր է, որ ՄԱԱՖՍԱ յուրաքանչյուր հիվանդի կլինիկական պատկերը մանրակրկիտ ուսումնասիրվի, որպեսզի հնարավոր լինի կանխատեսել հիվանդության հետագա զարգացումը, քանզի ակնհայտ է, որ ՁՓ ԱՖ-ի բարելավման հաճախա-կանությունը և աստիճանը կախված են հիմնականում ՍԱ-ի առաջացման պատճառից և տևողությունից [11,19,31,36]։ Օրինակ, Տակոցուբո կարդիոմիոպաթիայով հիվանդների մոտ հաճախ նկատվում է արագ բարելավում դեպի նորմալ ԱՖ արժեքներ, նույնիսկ դեղորայքային թերապիայի բացակայության դեպքում, և նրանք ունեն երկարաժամկետ բարվոք կանխատեսում [20]։ Սուր միոկարդիտով հիվանդների մոտ, որոնք կրիտիկական փուլն անցել են, հաճախ նկատվում է ՁՓ ԱՖ-ի վերականգնում: Պերիպարտալ կարդիոմիոպաթիան ևս գենետիկորեն պայմանավորված դիլատացիոն կարդիոմիոպաթիաների խմբից հանվել է, քանի որ այս տեսակն էլ ունի բավականին արագ վերականգնման հատկություն՝ մինչև ԱՖ-ի նորմալ արժեքներ [33,34]:…”
unclassified